Effects of Using Media of Chemondro and Video Conference on Teaching Learning towards Students’ Self-Efficacy and Students’ Self-Regulated Learning on the Subject of Hydrocarbon - Fitriyana, Nur; Ikhsan, Jaslin; Wiyarsi, Antuni; Sugiyarto, K. H. (EDUCATUM Journal of Science, Mathematics and Technology, 2018)
This research aimed to analyze the effect of using media in the teaching learning toward the aspects of students’ selfefficacy and students’ self-regulated learning. The media used were chemondro and video conference on the subject of hydrocarbon. This research was set as a quasi-experimental post-test only design. The population was the students of 11 public senior high school in Purworejo regency, Central Java, Indonesia. The sampling technique was two steps of cluster random sampling. The samples of this study were the six eleventh grade students (the mean age was 16) in two public senior high school in those regency. The samples were classified into three classes depending the media used in the teaching learning, they are Class CG-2 using chemondro only, Class CG-1 using hybrid of video conference only, and Class E using both chemondro and video conference. The data of students’ self-efficacy and students’ self-regulated learning were collected through questionnaire for each class. The data are analyzed according to MANOVA method, and it was found that there are significantly differences among the three classes for both aspects.